2021
DOI: 10.1021/acs.bioconjchem.1c00402
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Surface Modified Nanomaterials for Scavenging Reactive Oxygen Species in Organism

Abstract: Reactive oxygen species (ROS) are essential for normal physiological processes and play important roles in signal transduction, immunity, and tissue homeostasis. However, excess ROS may have a negative effect on the normal cells leading to various diseases. Nanomaterials are an attractive therapeutic alternative of antioxidants and possess an intrinsic ability to scavenge ROS. Surface modification for nanomaterials is a critical strategy to improve their comprehensive performances. Herein, we review the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 128 publications
0
6
0
Order By: Relevance
“…The buildup of oxygen radicals causes oxidative stress, which enhances inflammation in a variety of illnesses, including chronic inflammatory diseases and neoplasms (Meng et al, 2021; Reuter, Gupta, Chaturvedi, & Aggarwal, 2010). Also, diabetes, cardiovascular disease, and neurodegenerative diseases are all manifestations of chronic oxidative stress (Ma, Zhang, Chen, & Wang, 2021; Yao, Wang, & Li, 2022; Zhao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The buildup of oxygen radicals causes oxidative stress, which enhances inflammation in a variety of illnesses, including chronic inflammatory diseases and neoplasms (Meng et al, 2021; Reuter, Gupta, Chaturvedi, & Aggarwal, 2010). Also, diabetes, cardiovascular disease, and neurodegenerative diseases are all manifestations of chronic oxidative stress (Ma, Zhang, Chen, & Wang, 2021; Yao, Wang, & Li, 2022; Zhao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that as the SeNPs quantities rose from 6.5 to 106.3 mg/ml, scavenging capability improved dramatically from 48.45 ± 5.29 to 301.1 ± 11.42 mg/g. The SeNPs’ ability to neutralize these free radicals may be attributed to the dispersibility of the nanoparticles via media due to their tiny particle size, in addition to SeNPs’ high chemical activity [ 53 ]. The oxygen-releasing antioxidant might improve the adequacy with which cells multiply, migrate, proliferate, and spread, advancing the healing procedure.…”
Section: Resultsmentioning
confidence: 99%
“…PDA is also very efficient in complexing several metal ions and the effect of the presence of metals on the AOX properties has been recently reviewed [ 88 ]. Similarly, the general effect of surface functionalization on the ROS-scavenging ability has been discussed [ 89 ].…”
Section: Aox Properties Of Melanin Npmentioning
confidence: 99%